Pengaruh Kepuasan Gaji, Kepuasan Kerja, Serta Komitmen Organisasional Terhadap Intensi Keluar Di Hotel Sapta Nawa Gresik - Muhardiansyah, Doni; Kristanty, Irin (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2017)
High rate of turnover leads to adverse effect to an organization. Such problem is likely generating instability and uncertainty towards employment condition and human resources cost rise in forms of training invested to them, recruitment and newly built training programs. High turnover, in addition, also results in organizational ineffectiveness because it loses experienced employees as well as spends much times in training new, inexperienced employees. This study aims to analyze the effect of pay satisfaction, work satisfaction and organizational commitment on turnover intention and to analyze the most affective variable on turnover intention. There are 115 respondents for the samples and data analysis during the research is held by using SEM and AMOS program. According to the analysis, it is concluded as the followings: work satisfaction has a positive effect on organizational commitment with CR = 6,082, pay satisfaction has a negative effect on turnover intention with CR = -4,325, work satisfaction has a negative effect on turnover intention with CR = -4,905, and organizational commitment has a negative effect on turnover intention with CR = -2, 914. In efforts of decreasing turnover rate, Sapta Nawa Hotel Gresik jawa Timur should improve its pay rate granted to the employees, provide adequate financial aid to help the economy of the employees, to enhance relationship between employees and between employees and superiors, to give opportunity to any employee to improve his or her quality through formal education, to strengthen loyalty to company by fulfilling needs and intention of the employees, and to give rise to employees’ awareness that they have significant roles in supporting the company’s development.